The General Election Commission Strategy Through Election Education in Increasing the Political Participation of Beginners Voters Based on Democracy Principles - Sari Soleha, Rully; Widodo, Urip; Sophia, Erna; Rahimia, Nisa; Akbar Hayat, Muzahid (International Journal of Law, Environment, and Natural Resources, 2022)
This study aims to examine the General Election Commission’s strategy through election education in increasing the political participation of new voters based on democratic principles. This research is a qualitative research. The results of this study indicate that novice voters basically need political education regarding elections held by the General Elections Commission. The condition of beginner voters who are still vulnerable to negative politics is certainly an obstacle to the progress of democracy in Indonesia. With political education for novice voters, of course the expected results at the upcoming democratic party in 2024 are increasing awareness of young voters.